Cultural variants of fusaria from oil palm habitats - Ho, Yin Wan; Varghese, George (Universiti Pertanian Malaysia, 1988)
Variation in cultural and morphological characteristics existed in both the parent isolates and subcultures of 8 species of Fusarium isolated from oil palm soils. Based on pigmentation, mycelial characters and conidial measurements, different "morphological types" from parent isolates within a species were distinguished. Constant subculturing of the parent isolates gave rise to various cultural variants. The variants were the slimy-pionnotal, mycelial and ropy types or were in the form ofpatches or sections which differed in pigmentation from the parent colony.